Mobile testing : an ASTQB-BCS foundation guide - Black, Rex, 1964- (BCS, the Chartered Institute for IT, 2018)
Mobile testing is the process of testing the functionality, usability and consistency of mobile software. With this essential guide, in line with the ASTQB Certified Mobile Tester syllabus, you will gain the understanding and skills you require to begin your journey to becoming a proficient mobile tester.